Ischemia–Reperfusion Injury and Immunosuppressants Promote Polyomavirus Replication Through Common Molecular Mechanisms - Chen, Xu-Tao; Huang, Yang; Wang, Jing; Li, Ge; Zhang, Yu; He, Li-Fang; Lian, Yue-Xiao; Yang, Shi-Cong; Zhao, Guo-Dong; Zhang, Hui; Qiu, Jiang; Zhang, Lei; et al. (Frontiers in Immunology, 2022)
Background BK polyomavirus-associated nephropathy (BKPyVAN) causes renal allograft dysfunction and graft loss. However, the mechanism of BK polyomavirus (BKPyV) replication after kidney transplantation is unclear. Clinical studies have demonstrated that immunosuppressants and renal ischemia-reperfusion injury (IRI) are risk factors for BKPyV infection after kidney transplantation. Studying the pathogenic mechanism of BKPyV is limited by the inability of BKPyV to infect animal. Mouse polyomavirus (MPyV) is a close homologue of BKPyV. They have a lot in common in terms of gene structure and biological function. We used a model of MPyV infection to investigate the core genes and underlying mechanism of IRI and immunosuppressants to promote polyomavirus replication. Methods One-day-old male C57BL/6 mice were intraperitoneally injected with MPyV. At week 9 post-infection, all mice were randomly divided into IRI, immunosuppressants, and control groups and treated accordingly. IRI was established by clamping the left renal pedicle for 30 minutes. Subsequently, kidney specimens were collected for detecting MPyV DNA, histopathological observation, and high-throughput RNA sequencing. Weighted gene correlation network analysis (WGCNA), protein-protein interaction network analysis, and KEGG pathway enrichment analysis were used to screen for core genes and common signaling pathways involved in the process of promoting MPyV replication by IRI and immunosuppressants. Results After primary infection, MPyV established persistent infection in the kidneys and subsequently were significantly increased by IRI or immunosuppressants treatment individually. In IRI group, viral loads peaked on day 3 in the left kidney, which were significantly higher than that in the right kidney and the control group. In immunosuppressants group, viral loads in the left kidney were significantly increased on day 3, which were significantly higher than that in the control group. Protein-protein interaction network analysis and WGCNA screened complement C3, EGFR, and FN1 as core genes. Pathway enrichment analysis based on the IRI or immunosuppressants related genes selected by WGCNA indicated that NF-κB signaling pathway was the main pathway involved in promoting MPyV replication. The core genes were further confirmed using published datasets GSE47199 and GSE75693 in human polyomavirus-associated nephropathy. Conclusions Our study demonstrated that IRI and immunosuppressants promote polyomavirus replication through common molecular mechanisms.